A (1+3)-dimensional Boiti-Leon-Manna-Pempinelli Equation: Symmetry Reductions; Exact Solutions; Conservation Laws - Moroke, M. C.; Muatjetjeja, B.; Adem, A. R. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, a (1+3)-dimensional Boiti-Leon-Manna-Pempinelli equation is investigated. Exact solutions are acquired using the Lie symmetry method and multiple exp-function method via symbolic computation. In addition to exact solutions, we also present conservation laws and their physical ramifications are also discussed. The obtained results enlarge the known category of solutions of the (1+3)-dimensional Boiti-Leon-Manna-Pempinelli equation.